Analysis of Path Model Effect of Beliefs About The Nature of Mathematics on Beliefs About Teaching and Teacher Professional Characteristics Using PLS-SEM - Fariha, Mutia; Johar, Rahmah; Oktavia, Rini; Mailizar, Mailizar (Al-Khawarizmi, 2024)
Beliefs about Beliefs about the nature of mathematics can impact teachers' confidence in teaching math and their professional development. A study with 187 elementary school teachers in Banda Aceh showed that these beliefs have a significant direct effect on increasing beliefs about teaching math but only a minimal direct effect on improving teachers' professional character. Beliefs about teaching act as an indirect-only mediation variable between beliefs about the nature of mathematics and teacher characteristics, suggesting a high and significant indirect effect. Further research is needed to confirm these results